Deposition Hydroxyapatite /Titania Composite on Ti-6Al-7Nb Alloy for Human Body Implants - Hamdi, Dunya Abdulsahib (Al-Nahrain Journal for Engineering Sciences, 2018)
The microstructural analysis and electrochemical measurements tests were used to investigate the behaviors of (TiO2) and (HAp)-coated Ti-6Al-7Nb alloy in the SBF solution .By using RF sputtering, a thin TiO2 layer coated  the substrate, while a thick layer of HAp coated the outer side of surface. The generated middle layer consist of  the  composite of TiO2 and HAp which is by AFM characterized as uniformly distributed coating system with nano size. The images of the scan electron microscopy (SEM) shows that there is no any cracking observed in the outer layer of tested samples due to the use of thin film TiO2 as mid lead to reduce the difference in the thermal expansion between the HAp material and Ti-6Al-7Nb substrate .The HAp upper layer significantly improve the bioactivity of the Ti-6Al-7Nb alloy. In this study, the bonding strength and the corrosion resistance was improved by using thin layer of TiO2. From electrochemical impedance spectroscopy (EIS) study Bod plot, the composite layer of TiO2 and HAp was suggested by the capacitive act as barrier layer coated substrate and prevent the relays of the ion from metallic. The results shows the values of Rox (309.2 k? cm2)are greater than for Rct(19.2 k? cm2), by assumes the presence  oxide film increases for coated substrate are greater than that of uncoated, which is a result of the presence of coated film that improve the corrosion resistance of the sample.